Peningkatan Ketahanan Pakcoy terhadap Cekaman Kekeringan Melalui Aplikasi Biochar dan Pupuk Guano - Maximus Seran; Pareira, Magdalena Sunarty (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This research aims to determine the effect of using biochar and guano fertilizer on the growth and resistance of pakcoy to drought stress and it is hoped that this research will add information for the development of pakcoy plant cultivation techniques that are more adaptive to dry land. The method used in this research was a 2 factorial completely randomized plan. The first factor is providing Biochar (B) which consists of 4 levels: B0= Control 0 tons/ha, B2= Biochar 5 tons/ha, B3= Biochar 10 tons/ha, B4= Biochar 15 tons/ha. The second factor is the application of Guano fertilizer (G) which consists of 4 levels: G0= control 0 tons/ha, G2= Guano 5 tons/ha, G3= Guano 10 tons/ha, G4= Guano 15 tons/ha. . Based on the level of treatment used, 16 combinations were obtained, BOGO, BOG2, BOG3, BOG4, B2GO, B2G2, B2G3, B2G4, B3GO, B3G2, B3G3, B3G4, B4GO, B4G2, B4G3, B4G4, which were repeated 3 times so that there were 48 experimental units. The parameters observed include plant height, number of leaves and stem diameter. The results of the research showed that there was an interaction between plant height at 7 dap, 14 dap, 21 dap, 28 dap, number of leaves at 7 dap, 14 dap, 21 dap and stem diameter at 14 dap and 28 dap. Treatment with biochar rates of 10 tons/ha, 15 tons/ha and guano fertilizer 10 tons/ha, 15 tons/ha gave good growth results in plant height, number of leaves and stem diameter. This combination of two treatments can increase the efficiency of good nutrient uptake for optimal vegetative plant growth and can increase the soil's capacity to retain air and nutrients, while guano fertilizer provides essential nutrients that support the development of pak choy plants.